Information and communication technology and user knowledge-driven innovation in services - Hong Y. Park; Il-Hyung Cho; Sook Jung; Dorrie Main; Mark Goh (Cogent Business & Management, 2015)
User knowledge has been an important source of novel product development and innovation, but gathering accurate user knowledge has been time consuming and difficult because user knowledge is tacit and globally dispersed. However, information and communication technology can expand the boundaries by making user knowledge easier and less expensive to access. Structures and organizations are emerging to perform the task of user information gathering. This paper examines the nature of user knowledge and the emergence of a new system/structure for user knowledge gathering and user involvement in innovation. Three case studies of business innovation in three different organizations illustrate the ways that the organization matches the type of innovation with the characteristics of user knowledge. User involvement can occur either through direct input or via feedback provided after customers received services. User input can also be either proactive or reactive. User knowledge is often employed to monitor service workers also, which has significantly contributed to recent improvement in service quality. The cases presented support our proposition.
Keywords: 650